Pengintegrasian Penyimpanan Google Drive Pada Pembangunan Aplikasi Monitoring Project Menggunakan pyDrive - Devylia Todingbua; Nina Setiyawati (STMIK Budi Darma, 2022)
In a company that works on many projects, a system that can be used to monitor progress is needed. Monitoring is an assessment activity that is carried out continuously to see the progress of a task. Monitoring is important to make sure the project that is being carried out can run well. In this research, a Monitoring Project application was built using the Agile Software Development method. The application is made to make data managing and progress monitoring easier. In addition, a feature will be added to store and share project file access rights to the team members so that the files related to the project can be properly centralized. The application is built using the Python Flask and Webix Javascript framework. The application will be integrated with Google Drive storage using Google Drive API. The integration will be done with the help of the pyDrive library which can simplify Google's OAuth 2.0 authentication. pyDrive also warps the functions of the Google Drive API so the program code becomes more object-oriented. Applications then will be tested using the black box method which focuses on testing the application functions. Based on the testing results, the application can be used to do monitoring projects and help users in sharing project files with fellow team members. The Monitoring Project Application from this research can be used to monitor project progress and share project drive with team members